Development of Ciprofloxacin-Loaded Bilosomes In-Situ Gel for Ocular Delivery: Optimization, In-Vitro Characterization, Ex-Vivo Permeation, and Antimicrobial Study - Omar Awad Alsaidan; Ameeduzzafar Zafar; Mohd Yasir; Sami I. Alzarea; Mohammed Alqinyah; Mohammad Khalid (Gels, 2022)
Conventional eye drops are most commonly employed topically in the eye for the management of bacterial conjunctivitis. Eye drops have a low corneal residence time and 90–95% of the administered dose is eliminated from the eye by blinking and the nasolacrimal drainage system. This problem can be minimized by formulating a mucoadhesive ocular in-situ gel system that undergoes sol-gel transition upon stimulation by temperature, pH, and ions. The goal of this study was to develop ciprofloxacin (CIP) loaded bilosomes (BLO) in-situ gel for the improvement of therapeutic efficacy. The BLO was prepared by the thin-film hydration method and optimized by the Box–Behnken design. Cholesterol (CHO), surfactant (Span 60), and bile salt (sodium deoxycholate/SDC) were used as formulation factors. The vesicle size (nm) and entrapment efficiency (%) were selected as responses (dependent factors). The optimized CIP-BLO (CIP-BLO-opt) formulation displayed a vesicle size of 182.4 ± 9.2 nm, a polydispersity index of 0.274, a zeta potential of −34,461.51 mV, and an entrapment efficiency of 90.14 ± 1.24%. Both x-ray diffraction and differential scanning calorimetry spectra did not exhibit extensive peaks of CIP in CIP-BLO-opt, revealing that CIP is encapsulated in the BLO matrix. The CIP-BLO-opt formulation was successfully incorporated into an in-situ gel system using a gelling agent, i.e., Carbopol 934P and hydroxyl propyl methyl cellulose (HPMC K100 M). CIP-BLO-opt in-situ gel formulation (CIP-BLO-opt-IG3) was evaluated for gelling capacity, clarity, pH, viscosity, in-vitro CIP release, bio-adhesive, ex-vivo permeation, toxicity, and antimicrobial study. The CIP-BLO-opt-IG3 exhibited satisfactory gelling properties with a viscosity of 145.85 ± 9.48 cP in the gelling state. CIP-BLO-opt-IG3 displayed sustained CIP release (83.87 ± 5.24%) with Korsmeyer–Peppas kinetic as a best-fitted model (R2 = 0.9667). CIP-BLO-opt-IG3 exhibited a 1.16-fold than CIP-IG and a 2.08-fold higher permeability than pure CIP. CIP-BLO-opt-IG3 displayed a significantly greater bio-adhesion property (924.52 ± 12.37 dyne/cm2) than tear film. Further, CIP-BLO-opt-IG3 does not display any toxicity as confirmed by corneal hydration (76.15%), histology, and the HET-CAM test (zero scores). CIP-BLO-opt-IG3 shows significantly higher (p < 0.05) antimicrobial activity against P. aeruginosa and S. aureus than pure CIP. From all these findings, it could be concluded that CIP-BLO-opt-IG3 might be an effective strategy for the increment of corneal residence time and therapeutic activity of CIP.